Processos de subjetivação, corpos negros e cabelos crespos : estudantes negras em aliança - Almeida, Poliane dos Passos (2019)
This research presents experiences of a school psychologist in meetings with students who participated in student groups at the Federal Institute of Espírito Santo (IFES), Campus Linhares. Research purpose was to understand how some students’ struggles issues engender subjective production; understanding how students resist schooling body production and how they act by producing other ways of being together and inventing other ways of living in school; and this research also want to question how gender and race issues permeate the constitution of students’ subjectivity and school production. First of all we had meetings with IFES students from Campus Linhares, and written logbooks. Thus, the text is permeated by fragments of narratives from the stories of struggles, affections and relationships with bodies, and these narratives are linked with theoretical references, songs, poems and images. In this process, it was possible to see that alliance policies took place around demands for bodies to circulate in school. These struggles took place with own bodies, who took action as the means and ends of politics. Students created other ways of living together at school, and where there was silence around racist and sexist practices they occupied with their voices, lyrics and bodies. Finally, the research presents problematizations about race perception, and how it is engendered in Brazil, through the question of miscegenation, through some abolitionist movement stories and the movement against racism. The research intends to think about the brown ones power like an interlace, carries between the binary classifications. The research points out some considerations about racism in school, pointing out that the school institution, when functioning from the classificatory logic, meritocratic and excluding, operates a school necropolitics.